Polygamy in the context of family law and the crisis of civic responsibility - Taufik, Mirna; Damayanti, Nina; Giyanto, Giyanto (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
Polygamy among teenagers is an uncommon phenomenon in Indonesia, but it is prevalent in Musi Banyuasin Regency, South Sumatra. There are underlying factors contributing to this concerning trend among teenagers, which worries parents and continues to rise annually due to its potential impact on a child's future. Unfortunately, families often feel compelled to accept early polygamous marriages due to concerns about family honor. Despite the strict process mandated by family law, societal attitudes undermine this, leading to significant risks for those involved. Furthermore, the government's influence in implementing effective measures seems limited, highlighting an apparent lapse in civic responsibility. Therefore, this research aims to delve into the factors driving teenage polygamy and explore potential solutions that the local government and the community could pursue. The research methodology involves a qualitative approach with a focus on case studies. Purposive sampling was used to select 36 respondents, including ten polygamous teenage husbands, ten first wives, ten second wives, and six community figures. Data was collected through in-depth interviews. The research findings reveal a significant increase in teenage polygamous marriages in Musi Banyuasin Regency over the past decade. Factors contributing to this trend include premarital pregnancy, family economic conditions, societal misconceptions, and the influence of the polygamous environment.